Case Report: EBV Chronic Infection and Lymphoproliferation in Four APDS Patients: The Challenge of Proper Characterization, Therapy, and Follow-Up - Rivalta, Beatrice; Amodio, Donato; Milito, Cinzia; Chiriaco, Maria; Di Cesare, Silvia; Giancotta, Carmela; Conti, Francesca; Santilli, Veronica; Pacillo, Lucia; Cifaldi, Cristina; Desimio, Maria Giovanna; Doria, Margherita; et al. (Frontiers in Pediatrics, 2021)
Activated PI3K-kinase Delta Syndrome (APDS) is an autosomal-dominant primary immunodeficiency (PID) caused by the constitutive activation of the PI3KkinaseThe consequent hyperactivation of the PI3K-Akt-mTOR pathway leads to an impaired T- and B-cells differentiation and function, causing progressive lymphopenia, hypogammaglobulinemia and hyper IgM. Patients with APDS show recurrent sinopulmonary and chronic herpes virus infections, immune dysregulation manifestations, including cytopenia, arthritis, inflammatory enteropathy, and a predisposition to persistent non-neoplastic splenomegaly/lymphoproliferation and lymphoma. The recurrence of the lymphoproliferative disorder and the difficulties in the proper definition of malignancy on histological examination represents the main challenge in the clinical management of APDS patients, since a prompt and correct diagnosis is needed to avoid major complications. Targeted therapies with PI3K-Akt-mTOR pathway pharmacologic inhibitors (i.e. Rapamycin, Theophylline, PI3K inhibitors) represent a good therapeutic strategy. They can also be used as bridge therapies when HSCT is required in order to control refractory symptoms. Indeed, treated patients showed a good tolerance, improved immunologic phenotype and reduced incidence/severity of immune dysregulation manifestations. Here we describe our experience in the management of four patients, one male affected with APDS1 (P1) and the other three, a male and two females, with APDS2 (P2, P3, P4) presenting with chronic EBV replication, recurrent episodes of immune dysregulation manifestations and lymphomas. These cases highlighted the importance of a tailored and close follow-up, including serial endoscopic and lymph nodes biopsies control to detect a prompt and correct diagnosis and offer the best therapeutic strategy.